Neuroprotective effects of a medium chain fatty acid, decanoic acid, isolated from H. leucospilota against Parkinsonism in C. elegans PD model - Sanguanphun, Tanatcha; Sornkaew, Nilubon; Malaiwong, Nawaphat; Chalorak, Pawanrat; Jattujan, Prapaporn; Niamnont, Nakorn; Sobhon, Prasert; Meemon, Krai (Frontiers in Pharmacology, 2022)
Sea cucumbers are marine organism that have long been used for food and traditional medicine in Asian countries. Recently, we have shown that ethyl acetate fraction (HLEA) of the crude extract of the black sea cucumber, Holothuria leucospilota, could alleviate Parkinsonism in C. elegans PD models. In this study, we found that the effective neuroprotective activity is attributed to HLEA-P1 compound chemically isolated and identified in HLEA. We reported here that HLEA-P1 could attenuate DAergic neurodegeneration, improve DAergic-dependent behaviors, reduce oxidative stress in 6-OHDA-induced C. elegans. In addition, HLEA-P1 reduced α-synuclein aggregation, improved behavior deficit and recovered lipid deposition in transgenic C. elegans overexpressing α-synuclein. We also found that HLEA-P1 activates nuclear localization of DAF-16 transcription factor of insulin/IGF-1 signaling (IIS) pathway. Treatment with 25 μg/ml of HLEA-P1 upregulated transcriptional activity of DAF-16 target genes including anti-oxidant genes (such as sod-3) and small heat shock proteins (such as hsp16.1, hsp16.2 and hsp12.6) in 6-OHDA-induced worms. In α-synuclein-overexpressed C. elegans strain, treatment with 5 μg/ml of HLEA-P1 significantly activated mRNA expression of sod-3 and hsp16.2. Chemical analysis demonstrated that HLEA-P1 compound is decanoic acid/capric acid. Taken together, our findings revealed that decanoic acid isolated from H. leucospilota exerts anti-Parkinson effect in C. elegans PD models by partly modulating IIS/DAF-16 pathway.